The Experience of Social Alienation in Elderly Lung Cancer Patients: A Qualitative Study - Caini Song; Libo Yao (Elsevier, 2024)
Purpose: The aim of this study was to understand the experience of social alienation in elderly lung cancer patients, to explore its causes, and to propose targeted intervention strategies. Methods: From July to August 2023, 16 elderly lung cancer patients attending the respiratory department of a tertiary hospital in Changsha City, Hunan Province, were selected for semi-structured interviews using a purposive sampling method. The Colaizzi 7-step method was used to analyze the data. Results: A total of four themes were distilled: the experience of social alienation in elderly lung cancer patients (pessimistic feelings, inferiority complex, and heavy psychological burden), subjective causes (disease-included shame, avoidant social behavior, and stigmatized labels), objective causes (isolated social states, and reduced amount of socialization), and rehabilitation support. Conclusion: The causes of social alienation in elderly lung cancer patients include multiple aspects of personal, family, and social support, and symptom management and psychological guidance should be strengthened for this population to construct a hospital-society-family triple-linkage care program to help patients recover.